Analisis Pengaruh Manuver Putar Balik Kendaraan Terhadap Kinerja Arus Lalu Lintas Pada Ruas Jalan Sultan Alauddin - Soplantila, Willy Elias David; Nurdin, Abd Rahim; Mallawangeng, Tamrin (Jurnal Penelitian Teknik Sipil Konsolidasi, 2026)
This deceleration will affect the traffic flow in the same direction, this turning movement will cause high traffic volume, lower vehicle speeds, and higher density on the road section. The purpose of the study was to determine the performance of U-Turns and the level of road service equipped with U-Turn facilities, measure the average travel time of vehicles doing U-Turns, the speed of vehicles when doing U-Turns and the length of the queue doing U-Turn activities. To achieve these objectives, the PKJI 2023 method was used. From the results of the study, it was obtained that the Performance of the Road Section on Jalan Sultan Alauddin was 2640.25 skr/hour for traffic volume towards Gowa and 2881.50 skr/hour for traffic volume towards Makassar, for capacity with a degree of saturation of 0.77 for the Makassar - Gowa direction and 0.84 for the Gowa - Makassar direction. The conclusion of the research results shows that the Performance of Jalan Sultan Alauddin, Makassar City based on PKJI 2023 is 2465 skr/hour for Opening 1 and 2762 skr/hour for opening 2 and 2475 skr/hour for opening 2 for capacity with a degree of saturation of 0.72 for Opening 1 and 0.81 for Opening 2 and 0.73 for Opening 3.